Choroid Melanoma Metastasis to Spine: A Rare Case Report. (18th February 2016) - Mandaliya, Hiren; Singh, Nandini; George, Sanila; George, Mathew
Abstract : Metastatic choroid melanoma is a highly malignant disease with a limited life expectancy. The liver is the most common site for metastasis of uveal melanoma followed by lung, bone, skin, and subcutaneous tissue. Metastasis from choroidal melanoma usually occurs within the first five years of treatment for primary tumours. Metastatic choroid melanoma to the spine/vertebrae is extremely rare. We report the first case of spinal metastasis from choroid melanoma in a 61-year-old man who had been treated for primary ocular melanoma three years earlier with radioactive plaque brachytherapy. Synchronously, at the time of metastasis, he was also diagnosed as having a new primary lung adenocarcinoma as well. The only other case reported on vertebral metastasis from malignant melanoma of choroid in literature in which primary choroid melanoma was enucleated.